Understanding E-Money Preferences Among Students: A Case Study at FEBI UIN Ar-Raniry, Banda Aceh, Indonesia - Muksalmina, Muksalmina; Ahmadsyah, Israk; Dianah, Azimah (Graha Primera Saintifika, 2024)
As digital financial transactions continue to gain traction globally, understanding the factors that influence the adoption of electronic money (e-money) is crucial. This research paper delves into the behavioral aspects behind the use of e-money within a specific academic community. In a quantitative study carried out at Ar-Raniry State Islamic University's Faculty of Islamic Economics and Business (FEBI), we investigated the impact of utility, convenience, and security on students' interest in selecting e-money as their preferred payment method. The randomized sample of 97 students represented the faculty's diverse population. Our findings emphasize the critical roles of utility and convenience in shaping students' interest in e-money adoption, with attributes like speed, efficiency, and practicality significantly driving their embrace of electronic payment solutions. The research underscores the importance of designing e-money systems that prioritize utility and convenience to attract users, particularly in educational settings, while also providing insights for policymakers and financial institutions seeking to promote digital financial inclusion.